Evaluation of Selected Plant Phenolics via Beta-Secretase-1 Inhibition, Molecular Docking, and Gene Expression Related to Alzheimer’s Disease - Tugba Uçar Akyürek; Ilkay Erdogan Orhan; F. Sezer Şenol Deniz; Gokcen Eren; Busra Acar; Alaattin Sen (Pharmaceuticals)
Background: The goal of the current study was to investigate the inhibitory activity of six phenolic compounds, i.e., rosmarinic acid, gallic acid, oleuropein, epigallocatechin gallate (EGCG), 3-hydroxytyrosol, and quercetin, against β-site amyloid precursor protein cleaving enzyme-1 (BACE1), also known as β-secretase or memapsin 2, which is implicated in the pathogenesis of Alzheimer’s disease (AD). Methods and Results: The inhibitory potential against BACE1, molecular docking simulations, as well as neurotoxicity and the effect on the AD-related gene expression of the selected phenolics were tested. BACE1 inhibitory activity was carried out using the ELISA microplate assay via fluorescence resonance energy transfer (FRET) technology. Molecular docking experiments were performed in the human BACE1 active site (PDB code: 2WJO). Neurotoxicity of the compounds was carried out in SH-SY5Y, a human neuroblastoma cell line, by the Alamar Blue method. A gene expression analysis of the compounds on fourteen genes linked to AD was conducted using the real-time polymerase chain reaction (RT-PCR) method. Rosmarinic acid, EGCG, oleuropein, and quercetin (also used as the reference) were able to inhibit BACE1 with their respective IC50 values 4.06 ± 0.68, 1.62 ± 0.12, 9.87 ± 1.01, and 3.16 ± 0.30 mM. The inhibitory compounds were observed to occupy the non-catalytic site of the BACE1. However, hydrogen bonds were found to be present between rosmarinic acid and EGCG and aspartic amino acid D228 in the catalytic site. Oleuropein and quercetin effectively suppressed the expression of PSEN, APOE, and CLU, which are recognized to be linked to the pathogenesis of AD. Conclusions: The outcomes of the work bring quercetin, EGCG, and rosmarinic acid to the forefront as promising BACE1 inhibitors.